2003
DOI: 10.1016/s0002-9440(10)63803-5
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblastic Oxidative Stress in Relation to Temporal and Regional Differences in Maternal Placental Blood Flow in Normal and Abnormal Early Pregnancies

Abstract: Onset of the maternal-placental circulation was studied by Doppler ultrasonography in 65 pairs of agematched normal and abnormal pregnancies. In normal pregnancies intervillous blood flow increased with gestational age, being detected in 9 of 25 cases at 8 to 9 weeks but in 18 of 20 at 12 to 13 weeks (P ‫؍‬ 0.001). By contrast, in abnormal pregnancies flow was detected in nearly all cases (22 of 25) at 8 to 9 weeks (P < 0.001). In addition, regional differences were observed between the groups. Early flow was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
285
1
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 457 publications
(317 citation statements)
references
References 37 publications
(52 reference statements)
12
285
1
13
Order By: Relevance
“…As the gestational sac grows during fetal life, the villi that are associated with the decidua capsularis surrounding the amniotic sac degenerate and form the chorion leave, whereas villi that are associated with the decidua basalis proliferate and form the definitive placenta. 7 We previously have shown that the underlying uteroplacental circulation in the center of the primitive placenta is plugged, whereas in periphery the mouth of the spiral arteries are never plugged by the trophoblastic shell, which allows limited maternal blood flow to enter the marginal zone of placenta from 8-9 weeks of gestation. 8 This leads to higher local O 2 concentration at a stage of pregnancy when the trophoblast possesses low concentrations of the main antioxidant enzymes superoxide dismutase, catalase, and glutathione peroxidase.…”
Section: Commentmentioning
confidence: 99%
See 3 more Smart Citations
“…As the gestational sac grows during fetal life, the villi that are associated with the decidua capsularis surrounding the amniotic sac degenerate and form the chorion leave, whereas villi that are associated with the decidua basalis proliferate and form the definitive placenta. 7 We previously have shown that the underlying uteroplacental circulation in the center of the primitive placenta is plugged, whereas in periphery the mouth of the spiral arteries are never plugged by the trophoblastic shell, which allows limited maternal blood flow to enter the marginal zone of placenta from 8-9 weeks of gestation. 8 This leads to higher local O 2 concentration at a stage of pregnancy when the trophoblast possesses low concentrations of the main antioxidant enzymes superoxide dismutase, catalase, and glutathione peroxidase.…”
Section: Commentmentioning
confidence: 99%
“…8 This leads to higher local O 2 concentration at a stage of pregnancy when the trophoblast possesses low concentrations of the main antioxidant enzymes superoxide dismutase, catalase, and glutathione peroxidase. 7 Focal trophoblastic oxidative damage and progressive villous degeneration trigger the formation of fetal membranes, which remodels the uteroplacental interface. First-trimester vaginal bleeding has been associated with increased maternal levels of free serum ␤-hCG, 41 possibly because of a rise in hCG transfer into the maternal circulation because of the disruption of the maternofetal interface.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Inefficient invasion of the spiral arteries can induce an unresolved placental oxidative stress and lead to pre-eclampsia [5,8,22]. Due to the occlusion of the maternal vessels by trophoblasts, the initial gradient of oxygen partial pressure between the mother (where it amounts to around 50-100 mm Hg) and the embryo (where it amounts to around 14 mm Hg) is maintained after the 8th week of gestation and evolves slowly to 39.6 mm Hg at a gestational age of 10 weeks [38,52,54], the complete transformation of the spiral arteries being achieved only between weeks 18 and 20 of gestation [55]. In the conceptus, the low initial oxygen partial pressure evolves only slowly between the 10th and 16th week of pregnancy from 64.3 to 73.2 mm Hg at the level of decidua, from 25.6 to 56.2 mm Hg at the level of the placenta, and, remains unchanged during this interval at the level of the coelomic fluid, i.e.…”
Section: Oxygen Partial Pressure As a Factor Of Ros Production Duringmentioning
confidence: 99%